Hubungan Kebiasaan Makan Pagi (Sarapan) Dengan Status Gizi Anak Usia Sekolah Di SD Muhammadiyah Terpadu Ponorogo - Siti Munawaroh; Elmie Muftiana; Yayuk Dwirahayu (Jurnal Keperawatan Muhammadiyah, 2020)
Objective: Elementary school age children nutrition problems are the impact of an imbalance between food intake and nutrients released by the body. This can be caused by not having breakfast habits. Eating breakfast has the benefit of maintaining endurance and increasing learning concentration. The breakfast habit provides the energy and nutrients needed to carry out various activities throughout the day such as school, study, and play optimally. This study aims to determine the relationship between breakfast habits and nutritional status of elementary school children.Methods: This research was conducted at SD Muhammadiyah Terpadu Ponorogo class 4 and 5 with a sample of 113 students. The measuring instrument used was a questionnaire to explore the variables of breakfast habits, while to determine the nutritional status of students using a weighing scale. Nutritional status was calculated IMT/U. The bivariate analysis test used the Chi Square test of significance level 0.05Results: Chi square test results obtained p-value 0.406 means that there is no relationship between breakfast habits and nutritional status of school age children at SD Muhammadiyah Terpadu Ponorogo. Many factors influence nutritional status. Respondents do not usually eat breakfast, but during recess they eat by buying a canteen and in their daily life they like to eat vegetables and fruit so there is no problem with nutritional intake.Conclusion: Researchers recommend to the next researchers to dig deeper about the composition of the food at the time the respondent had breakfast.